The Final Scene of Hyenas A Parenthetical Incorporation - Eshun, Kodwo (Re-visiones, 2024)
Hyenas tends to be characterised as a “biting satire of today’s Africa’” that has betrayed the hopes of independence for the false promises of Western materialism. A reading such as this interprets Hyenas as an Afropessimist fabulation of the formation of the neocolony in which the victory of materialism over self-determination is staged as the subsumption of Pan-Africanist morality by the modernity of the International Monetary Fund. This reading turns upon an interpretation of the final scene in Hyenas in which the passage from poverty to wealth promised by Linguere Ramatou is instituted through the sentence of death visited by the townspeople of Colobane upon the grocer Draman Drameh, the subject that accepts his guilt. In the present text, Kodwo Eshun argues for a different understanding. He posits that the final scene in Hyenas can be understood not as a murder, nor as a sacrifice, but more precisely, as an act of occluded incorporation by a corporate personhood whose opacity does not thwart transparency or universality, as Edouard Glissant proposed, but instead acts as the fatal precondition for integration into world capitalism.